Endorsement and embodiment of cautiousness-related age stereotypes - Huang, Tingting; Rothermund, Klaus (Frontiers in Psychology, 2023)
Endorsement of implicit age stereotypes was assessed with the propositional evaluation paradigm (PEP) in a high-powered, preregistered study, comprising samples of young (n = 89) and older (n = 125) adults. To investigate whether implicit age stereotypes shape the behavior via self-stereotyping (“embodiment”), we examined whether implicit endorsement of the belief of older (young) people being cautious (reckless) predicts older (young) individuals’ spontaneous behavior in a speeded response time task. In both age groups, we found significant implicit endorsement effects of age stereotypical beliefs. However, implicit endorsement effects of the cautiousness-related age stereotypes were unrelated to our indicators of spontaneous cautious/reckless behavior in the speeded RT task (as assessed with the parameter a of a diffusion model analysis) for both age groups. The same pattern of results (endorsement of age stereotypic beliefs but no relation with behavioral indicators) was found for explicit measures of age stereotypes. Replicating previous findings, implicit and explicit measures of cautiousness-related age stereotypes were uncorrelated. In sum, our findings provide evidence for the implicit and explicit endorsement of cautiousness-related stereotypical beliefs about old and young people; individual differences in belief endorsement, however, did not predict differences in spontaneous cautiousness-related behavior in a speeded RT task.